Age-Related Changes in Immune Cells of the Human Cochlea - Noble, Kenyaria V.; Liu, Ting; Matthews, Lois J.; Schulte, Bradley A.; Lang, Hainan (Frontiers in Neurology, 2019)
Age-related hearing loss is a chronic degenerative disorder affecting one in two individuals above the age of 75. Current population projections predict a steady climb in the number of older individuals making the search for interventions to prevent or reverse this disorder even more critical. There is growing acceptance that aberrant activity of resident or infiltrating immune cells, such as macrophages, is a major factor contributing to the onset and progression of age-related degenerative diseases. However, how macrophage populations and their functionally-driven morphological characteristics change with age in the human cochlea remains largely unknown. In this study, we employed immunohistochemical approaches along with confocal and super-resolution imaging, three-dimensional reconstructions, and quantitative analysis to determine age-related changes in macrophage numbers and morphology as well as interactions with other cell-types and structures of the auditory nerve and lateral wall in the human cochlea. In the cochlea of human ears from young and middle aged adults those macrophages in the auditory nerve assumed a worm-like structure in contrast to those in the spiral ligament or associated with the dense microvascular network in the stria vascularis which exhibited a highly ramified morphology. Macrophages in both the auditory nerve and cochlear lateral wall showed morphological alterations with age. The population of activated macrophages in the auditory nerve increased in cochleas obtained from older donors. Dual-immunohistochemical staining with macrophage, myelin, and neuronal markers revealed increased interactions of macrophages with the glial and neuronal components of the aged auditory nerve. These findings implicate the involvement of abnormal macrophage-glia interactions in age-related physiological and pathological alterations in the human cochlea. There is clearly a need to further investigate the contribution of macrophage-associated inflammatory dysregulation in human presbyacusis.